Stormorken Syndrome Caused by a Novel STIM1 Mutation: A Case Report - Jiang, Li-Jun; Zhao, Xue; Dou, Zhi-Yan; Su, Qing-Xiao; Rong, Zan-Hua (Frontiers in Neurology, 2021)
Objective: To identify the gene mutation of Stormorken syndrome and review the published Stromal Interaction Molecule 1 (STIM1) mutations phenotype. Methods: We described the clinical and molecular aspects of a 12-year-old female with Stormorken syndrome. Then we summarized all the mutation sites reported in literature. We reviewed the clinical features of published cases with gain of function mutations of STIM1. Results: A 12 years old Chinese female presented with skin purpura in the lower limbs and stroke-like episodes. Muscle biopsy and microscopic examination revealed atrophy in her skeletal muscle. Genetic analysis identified a novel heterozygous missense mutation, a c.1095G>C transition (NM_003156.3), which caused a p.K365N amino acid substitution in the protein and affected a STIM1-orail-activation region (SOAR). Conclusions: The novel mutation c.1095G>C transition (NM_003156.3) was located in the SOAR. However, mutations reported so far in STIM1 reside in the EF hand region, CC1 domain or CTID. The findings expand the phenotypic spectrum of STIM1 mutations human disorders and define the molecular basic of Stormorken syndrome.